PENGARUH CORPORATE GOVERNANCE, KOMPENSASI RUGI FISKAL, RETURN ON ASSETS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Students' Journal of Accounting and Banking, 2014)
This study examines the effect of Corporate Governance, fiscal lost compensation, Return on Assets, Leverage and firm’s size to Tax Avoidance. Corporate Governance are showed from compotition of Independen Commisioner and Audit Comite. This research was conducted at the Indonesian Stock Exchange by using a go public and listing manufacturing company as the unit of analysis during periode from 2010 to 2012.Data are used on this study is secondary data be obtained from Indonesia Stock Exchange (IDX) a financial statements and Indonesian Market Directory data type of manufacturing company during periode from 2010-2012. The sampling method used purposive sampling with the observation periode from 2010-2012. Relationship and influence between variable is described by using multiple regression analysis. The results showed that the compotition of independen commissioner and fiscal lost compensation has positive effect and significant to the tax avoidance. Whereas the audit comite, return on asset, leverage and firm’s size had no significant effect on tax avoidance. Keywords: Corporate Governance, Fiscal Lost Compensation, Firm’s size and Tax Avoidance